Pendampingan Dasar-Dasar Penggunaan Microsoft Office untuk Mahasiswa Magang STIE Alwashliyah Sibolga - Batubara, Muhammad Iqbal; Koto, Mhd. Shafwan; Sikumbang, Amaludin; Basriyani, Anna; Kaharuddin, Kaharuddin (CV. Devi Tara Innovations, 2026)
The development of information technology requires students to possess adequate digital skills, particularly in the use of office software such as Microsoft Office. However, there are still internship students who have not optimally mastered basic applications such as Microsoft Word, Excel, and PowerPoint. This Community Service Program (PKM) aims to improve the competence of internship students at STIE Alwashliyah Sibolga through mentoring in the use of Microsoft Office. The methods used include training sessions, hands-on practice, and evaluation of participants’ abilities before and after the activity. The results show an improvement in students’ understanding and skills in creating documents, processing simple data, and preparing presentations. This activity is expected to support students’ readiness to face an increasingly technology-based workplace.